A ladder coordination polymer based on Ca2+ and (4,5-dicyano-1,2-phenylene)bis(phosphonic acid): crystal structure and solution-state NMR study - Venkatramaiah, Nutalapati (2017)
The preparation of coordination polymers (CPs) based on either transition metal centres or rare-earth cations has grown considerably in recent decades. The different coordination chemistry of these metals allied to the use of a large variety of organic linkers has led to an amazing structural diversity. Most of these compounds are based on carb{\-}oxy{\-}lic acids or nitro{\-}gen-containing ligands. More recently, a wide range of mol{\-}ecules containing phospho{\-}nic acid groups have been reported. For the particular case of Ca2+-based CPs, some inter{\-}esting functional materials have been reported. A novel one-dimensional Ca2+-based coordination polymer with a new organic linker, namely poly[[di{\-}aqua[$\mu$4-(4,5-di{\-}cyano-1,2-phenyl{\-}ene)bis{\-}(phospho{\-}nato)][$\mu$3-(4,5-di{\-}cyano-1,2-phenyl{\-}ene)bis(phospho{\-}nato)]{\-}dicalcium(II)] tetra{\-}hydrate], {[Ca2(C8H4N2O6P2)2(H2O)2]{\textperiodcentered}4H2O}n, has been prepared at ambient temperature. The crystal structure features one-dimensional ladder-like $\infty$1[Ca2(H2cpp)2(H2O)2] polymers [H2cpp is (4,5-di{\-}cyano-1,2-phenyl{\-}ene)bis{\-}(phospho{\-}nate)], which are created by two distinct coordination modes of the anionic H2cpp2{\textminus} cyano{\-}phospho{\-}nate organic linkers: while one mol{\-}ecule is only bound to Ca2+ cations via the phospho{\-}nate groups, the other establishes an extra single connection via a cyano group. Ladders close pack with water mol{\-}ecules through an extensive network of strong and highly directional O{\textemdash}H⋯O and O{\textemdash}H⋯N hydrogen bonds; the observed donor{\textendash}acceptor distances range from 2.499 (5) to 3.004 (6) {\AA} and the inter{\-}action angles were found in the range 135{\textendash}178{\textdegree}. One water mol{\-}ecule was found to be disordered over three distinct crystallographic positions. A detailed solution-state NMR study of the organic linker is also provided.